2004
DOI: 10.1103/physreve.69.045104
|View full text |Cite
|
Sign up to set email alerts
|

Model for cascading failures in complex networks

Abstract: Large but rare cascades triggered by small initial shocks are present in most of the infrastructure networks. Here we present a simple model for cascading failures based on the dynamical redistribution of the flow on the network. We show that the breakdown of a single node is sufficient to collapse the efficiency of the entire system if the node is among the ones with largest load. This is particularly important for real-world networks with a highly hetereogeneous distribution of loads as the Internet and elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
611
4
18

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 992 publications
(640 citation statements)
references
References 22 publications
7
611
4
18
Order By: Relevance
“…At this point we would like to mention other studies in which the resistance against cascades was studied as a function of geometrical disorder. In models based on critical loads and percolation in interdependent networks it was found that a heterogeneous network is less resistant against higher loads than a homogeneous one [12,13,14]. In our model degree heterogeneity (low γ) appears to strengthen the network at low a but to weaken it at high a.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…At this point we would like to mention other studies in which the resistance against cascades was studied as a function of geometrical disorder. In models based on critical loads and percolation in interdependent networks it was found that a heterogeneous network is less resistant against higher loads than a homogeneous one [12,13,14]. In our model degree heterogeneity (low γ) appears to strengthen the network at low a but to weaken it at high a.…”
mentioning
confidence: 75%
“…[8]. Avalanches in distribution models were also studied using sand piles on networks [9] and in various models based on critical loads [10,11,12,13]. Recently, also models studying percolation in interdependent networks were used [14].…”
Section: Construction Of a General Hamiltonianmentioning
confidence: 99%
“…The question is then under which conditions this failure leads to a cascade of macroscopic size. Applications of this case include power-grid cascade failures [4,5,10], or failures of server infrastructure [6].…”
Section: Results For the Rie Regimementioning
confidence: 99%
“…A fixed relation between fragility and threshold was first used in [4] to describe cascading processes in power grids and Internet (see also [5,9,10]). It basically reflects the situation of many socio-technical systems in which the capacity of agents is usually ad hoc designed to handle the load, because limited by cost, under normal conditions.…”
Section: /23mentioning
confidence: 99%
See 1 more Smart Citation